Human Immunodeficiency Virus-1 Latency Reversal via the Induction of Early Growth Response Protein 1 to Bypass Protein Kinase C Agonist-Associated Immune Activation - Wong, Lilly M.; Li, Dajiang; Tang, Yuyang; Méndez-Lagares, Gema; Thompson, George R.; Hartigan-O’Connor, Dennis J.; Dandekar, Satya; Jiang, Guochun (Frontiers in Microbiology, 2022)
Human Immunodeficiency Virus-1 (HIV) remains a global health challenge due to the latent HIV reservoirs in people living with HIV (PLWH). Dormant yet replication competent HIV harbored in the resting CD4+ T cells cannot be purged by antiretroviral therapy (ART) alone. One approach of HIV cure is the “Kick and Kill” strategy where latency reversal agents (LRAs) have been implemented to disrupt latent HIV, expecting to eradicate HIV reservoirs by viral cytopathic effect or immune-mediated clearance. Protein Kinase C agonists (PKCa), a family of LRAs, have demonstrated the ability to disrupt latent HIV to an extent. However, the toxicity of PKCa remains a concern in vivo. Early growth response protein 1 (EGR1) is a downstream target of PKCa during latency reversal. Here, we show that PKCa induces EGR1 which directly drives Tat-dependent HIV transcription. Resveratrol, a natural phytoalexin found in grapes and various plants, induces EGR1 expression and disrupts latent HIV in several HIV latency models in vitro and in CD4+ T cells isolated from ART-suppressed PLWH ex vivo. In the primary CD4+ T cells, resveratrol does not induce immune activation at the dosage that it reverses latency, indicating that targeting EGR1 may be able to reverse latency and bypass PKCa-induced immune activation.